2019
DOI: 10.1038/s41467-019-10018-1
|View full text |Cite
|
Sign up to set email alerts
|

Killer-like receptors and GPR56 progressive expression defines cytokine production of human CD4+ memory T cells

Abstract: All memory T cells mount an accelerated response on antigen reencounter, but significant functional heterogeneity is present within the respective memory T-cell subsets as defined by CCR7 and CD45RA expression, thereby warranting further stratification. Here we show that several surface markers, including KLRB1, KLRG1, GPR56, and KLRF1, help define low, high, or exhausted cytokine producers within human peripheral and intrahepatic CD4 + memory T-cell populations. Highest simultaneous pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 61 publications
(69 reference statements)
2
58
0
Order By: Relevance
“…5c). Genes ( KLRF1, FGFBP2, and PTGDS) upregulated in PA T-cells cluster within an offshoot off the main body of the UMAP plot suggesting a progression towards terminally differentiated effector memory T-cells in the PA. FGFBP2 is associated with T-cell effector functions 19 , and KLFR1 is a marker for CD4+ T-cell exhaustion and decline of cytokine releasing potential 20 . Its overexpression in the PA region suggests antigen-persistence occurs anatomically in atherogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…5c). Genes ( KLRF1, FGFBP2, and PTGDS) upregulated in PA T-cells cluster within an offshoot off the main body of the UMAP plot suggesting a progression towards terminally differentiated effector memory T-cells in the PA. FGFBP2 is associated with T-cell effector functions 19 , and KLFR1 is a marker for CD4+ T-cell exhaustion and decline of cytokine releasing potential 20 . Its overexpression in the PA region suggests antigen-persistence occurs anatomically in atherogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of CD4 + T EMRA cells have identified major subsets based on G protein-coupled receptor GPR56 expression, with virus-specific cells more frequently GPR56 + and more clonally expanded compared to GPR56 − cells ( 52 ). Increased expression of GPR56 and killer-like receptors (KLR) has been linked to higher cytokine expression by memory CD4 + T cells, including T cells obtained from liver tissue ( 53 ). CD4 + and CD8 + T EMRA cytotoxic T cells expressing GPR56 have also been associated with increased co-expression of CX 3 CR1 ( 52 , 54 , 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Virus-specific T EMRA cells are more frequently GPR56 + , 16 and increased expression of GPR56 and killer-like receptors (KLRs) has been linked to higher CD4 + T cell cytokine expression. 17 Furthermore, cytotoxic GPR56 + CD4 + and CD8 + T EMRA cells have higher co-expression of the CX3CR1 receptor, 16 , 18 , 19 which is also a marker of anti-cytomegalovirus (CMV) T cells. 19 , 20 , 21 , 22 Given that adipose tissue serves as a reservoir for latently HIV-infected CD4 + T cells, free HIV RNA virus, and CMV, 2 , 3 , 6 , 23 greater C-G-C + co-expression on CD4 + T cells in adipose tissue of HIV-positive diabetics may reflect a cytotoxic response by virus-specific cells that adversely affects bystander adipocytes and contributes to metabolic disease.…”
Section: Introductionmentioning
confidence: 99%